Paravertebral Cerebrospinal Fluid Exudation in Young Women with Postdural Puncture Headache: A Hypothetical Interpretation based on Anatomical Study on Intervertebral Foramen - Kawahara, Takashi; Atsuchi, Masamichi; Arita, Kazunori; Fujio, Shingo; Higa, Nayuta; Hanaya, Ryosuke (Asian Journal of Neurosurgery, 2023)
Background Postdural puncture headache (PDPH) is defined as a prolonged orthostatic headache secondary to a lumbar puncture. The mechanism underlying this unpleasant complication and the reasons explaining its higher incidence in the young are not well understood. Here, we speculate on the mechanisms underlying PDPH based on spinal magnetic resonance imaging (MRI) in patients with PDPH and an anatomical study on the size of the intervertebral foramen.Methods Brain and spinal MRI findings were examined in two young women with PDPH. The relationship between age and size of the intervertebral foramen on computed tomography was assessed in 25 female volunteers (22–89 years old) without spinal disease.Results The causative interventions leading to PDPH were epidural anesthesia for painless delivery in a 28-year-old woman and lumbar puncture for examination of the cerebrospinal fluid (CSF) in a 17-year-old woman. These two patients developed severe orthostatic hypotension following the procedure. Brain MRI showed signs of intracranial hypotension, including subdural effusion, in one patient, but no abnormality in the other. Spinal MRI revealed an anterior shift of the spinal cord at the thoracic level and CSF exudation into the paravertebral space at the lumbar level. Treatment involving an epidural blood patch in one patient and strict bed rest with sufficient hydration in the second led to improvement of symptoms and reduction of paravertebral CSF exudation. The size of the intervertebral foramen at the L2–3 level in the 25 volunteers showed a decrease in an age-dependent manner (Spearman's rho −0.8751, p < 0.001).Conclusion We suggest that CSF exudation from the epidural space of the vertebral canal to the paravertebral space through the intervertebral foramen, which is generally larger in the younger population, is the causative mechanism of PDPH.
Keywords: postdural puncture headache; PDPH; orthostatic headache; intervertebral foramen; paravertebral space